Development of Solar Biomass Drying System - Atnaw, Samson M.; C. K. M., Faizal; Oumer, Abduaziz Jama (EDP Sciences, 2017)
The purpose of this paper focuses on the experimental pre-treatment of biomass in agricultural site using solar energy as power source and contribution of common use and efficiency solar dryer system for consumer. The main purpose of this design for solar cabinet dryer is to dry biomass via direct and indirect heating. Direct heating is the simplest method to dry biomass by exposing the biomass under direct sunlight. The solar cabinet dryer traps solar heat to increase the temperature of the drying chamber. The biomass absorbs the heat and transforms the moisture content within the biomass into water vapour and then leaves the chamber via the exhaust air outlet. This problem however can be solved by adopting indirect solar drying system. High and controllable temperatures can be achieved as a fan is used to move the air through the solar collector. This project has successfully created a solar cabinet dryer that combines both direct and indirect solar drying systems and functions to dry biomass as well as crops effectively and efficiently with minimal maintenance. Hence, it is indeed a substitution for conventional dryers which are affordable to local farmers.